2015
DOI: 10.1038/nchembio.1788
|View full text |Cite
|
Sign up to set email alerts
|

Impeding the interaction between Nur77 and p38 reduces LPS-induced inflammation

Abstract: Sepsis, a hyperinflammatory response that can result in multiple organ dysfunctions, is a leading cause of mortality from infection. Here, we show that orphan nuclear receptor Nur77 (also known as TR3) can enhance resistance to lipopolysaccharide (LPS)-induced sepsis in mice by inhibiting NF-κB activity and suppressing aberrant cytokine production. Nur77 directly associates with p65 to block its binding to the κB element. However, this function of Nur77 is countered by the LPS-activated p38α phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
155
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 59 publications
4
155
0
2
Order By: Relevance
“…Ismail et al [46] and You et al [34] reported that, in ECs, NR4A1 inhibits NF-κB activation through up-regulation of IκBα (inhibitor of NF-κB α), by binding to an NR4A1-binding element in the IκBα promoter [34,46]. Another mechanism by which NR4A1 influences NF-κB activation is through direct interaction with the p65 subunit of NF-κB, and blocking p65 binding to its κB element to attenuate the production of pro-inflammatory cytokines [48,49]. These studies suggest that the orphan nuclear receptor NR4A1 is induced by inflammatory stimuli, and exerts an anti-inflammatory effects by suppressing NF-κB activity.…”
Section: Discussionmentioning
confidence: 94%
“…Ismail et al [46] and You et al [34] reported that, in ECs, NR4A1 inhibits NF-κB activation through up-regulation of IκBα (inhibitor of NF-κB α), by binding to an NR4A1-binding element in the IκBα promoter [34,46]. Another mechanism by which NR4A1 influences NF-κB activation is through direct interaction with the p65 subunit of NF-κB, and blocking p65 binding to its κB element to attenuate the production of pro-inflammatory cytokines [48,49]. These studies suggest that the orphan nuclear receptor NR4A1 is induced by inflammatory stimuli, and exerts an anti-inflammatory effects by suppressing NF-κB activity.…”
Section: Discussionmentioning
confidence: 94%
“…Both pro- and anti-inflammatory roles for Nr4a1 have been described in various functional settings, including its modulation of the NF-κB pathway 49,50 . Another Nr4a member, Nr4a2 (Nurr1), expressed in microglia and astrocytes, was shown to mediate neuroprotection by recruiting the CoREST transrepressor to promoters of NF-κB target genes 51 .…”
Section: Discussionmentioning
confidence: 99%
“…NR4A1 promotes and controls the early monocyte proinflammatory responses, which is required for the initiation of inflammatory resolution and subsequent monocyte-derived, macrophage-dependent reparative/healing phase. Similar molecular mechanisms are used in controlling immune homeostasis in LPS-induced sepsis to permit NR4A1-mediated control of hyperinflammatory responses (47). From such studies it is becoming evident that the local environment influences the differentiation stage/ function of immune cells, thus determining the cell-specific contribution NR4A receptors play in guiding the magnitude of inflammatory responses and outcomes (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, altering the expression level of these constitutively active receptors may be a feasible approach to modulate NR4A target genes in a cell-specific manner. The in vivo therapeutic potential of targeting NR4A/NF-kB interactions to control immune homeostasis has recently been uncovered (47). A chemical compound n-pentyl 2-[3,5-dihydroxy-2-(1-nonanoyl)-phenyl]acetate targets the ligand-binding domain of NR4A1 and prevents phosphorylation of NR4A1 by TLR-activated p38a.…”
Section: Discussionmentioning
confidence: 99%